Videolaringoestroboscopic characteristics of female teachers with vocal complaints (Research, Society and Development, 2020)
Objective: to verify the videolaryngostroboscopic characteristics of teachers with vocal complaints. Methods: 32 teachers with a mean of 39.15 years old underwent a medical examination of videolaryngostroboscopy. Videolaryngostroboscopies were evaluated by consensus and simultaneously by three otorhinolaryngologists using a specific protocol. Data were analyzed descriptively and by Spearman's Correlation test, with a significance level of 5% (p≤0.05). Results: most teachers had normal glottic closure (65.62%). All of them presented: high symmetry of vocal fold vibration (92.18%), high amplitude of mucosal wave vibration (90.31%), and high presence of mucous wave (90.93%). There was a significant positive correlation between normal glottic closure and amplitude of vibration (p=0.008) and between amplitude of vibration and mucosal wave (p=0). There was a significant negative correlation between altered glottic closure and amplitude of vibration (p=0.003); between altered glottic closure and normal closure (p=0); and between symmetry of vibration and global constriction of the laryngeal vestibule (p=0). Conclusion: the majority of teachers, even with vocal complaints and some with the presence of vocal nodules, had normal glottal closure and all had averages above 90% in the parameters: symmetry of vocal fold vibration, amplitude of mucosal wave vibration, and presence of mucous wave. In this group, the greater the normal glottic closure, the greater the amplitude of vibration of the mucous wave, and what the greater the presence of the wave, and the less the global constriction of the laryngeal vestibule, the greater the symmetry of vocal fold vibration.